2018
DOI: 10.1253/circj.cj-17-1085
|View full text |Cite
|
Sign up to set email alerts
|

Impact of B-Type Natriuretic Peptide Level on Risk Stratification of Thromboembolism and Death in Patients With Nonvalvular Atrial Fibrillation ― The Hokuriku-Plus AF Registry ―

Abstract: In a real-world cohort of Japanese NVAF patients, high BNP was significantly associated with TE and death. Plasma BNP might be a useful biomarker for these adverse clinical events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 22 publications
1
47
0
Order By: Relevance
“…Interhospital Cardiovascular Studies (Keio Study) (783 patients), 16 and Hokuriku-Plus AF Registry (1492 patients). 11 The data from each registry were collected and integrated in March 2016, and those from the Keio Study were updated in April 2018. A total of 819 patients with valvular AF and 3810 lacking complete data were excluded (Figure; eTable 1 in the Supplement).…”
Section: Keiomentioning
confidence: 99%
See 3 more Smart Citations
“…Interhospital Cardiovascular Studies (Keio Study) (783 patients), 16 and Hokuriku-Plus AF Registry (1492 patients). 11 The data from each registry were collected and integrated in March 2016, and those from the Keio Study were updated in April 2018. A total of 819 patients with valvular AF and 3810 lacking complete data were excluded (Figure; eTable 1 in the Supplement).…”
Section: Keiomentioning
confidence: 99%
“…The patient demographic characteristics of each registry have been published previously. 11,[13][14][15][16] Briefly, the J-RHYTHM Registry was a prospective, observational cohort study aiming to determine the current status of anticoagulation therapy in Japanese patients with AF. 13 A total of 7937 patients with AF, with or without warfarin treatment, from 158 institutions throughout Japan were registered between January and July 2009.…”
Section: Characteristics Of Each Registrymentioning
confidence: 99%
See 2 more Smart Citations
“…Their value in a variety of cardiovascular diseases such as myocardial infarction and heart failure have previously been established (80,81). Further studies have also consistently demonstrated that levels of these biomarkers may be used to improve predictions of stroke risk in AF (57,62,(65)(66)(67)71). A RE-LY sub-study found that elevations in troponin I and N-terminal pro-B-type natriuretic peptide (NT-proBNP) were common among AF patients (66).…”
Section: Cardiac Functionmentioning
confidence: 99%